FUNDACIÓN CIAT - Agronatura (International Center for Tropical Agriculture, 2012)
The CIAT Management Team proposed the creation of an independent, not-for-profit entity that would contribute more effectively and efficiently to CIAT's mission in Latin America and the Caribbean (LAC).